Fractal characteristics of shale pore structure and its influence on seepage flow. Issue 5 (19th May 2021) - Wang, Shengwei; Li, Xijian; Xue, Haiteng; Shen, Zhonghui; Chen, Liuyu
Abstract : The migration law of shale gas has a significant influence on the seepage characteristics of shale, and the flow of the gas is closely related to the pore structure. To explore the influence of shale pore parameters on permeability in different diffusion zones, the pore structure of the shale in the Niutitang Formation in Guizhou, China, was analysed based on liquid nitrogen adsorption experiments and nuclear magnetic resonance experiments. The relationship among fractal dimension, organic carbon content (TOC) and BET-specific surface area was analysed based on the fractal dimension of shale pores calculated using the Frenkel–Halsey–Hill model. Shale permeability was calculated using the Knudsen number ( Kn ) and permeability equation, and the influence of the fractal dimension and porosity in different diffusion zones on shale permeability was analysed. Previous studies have shown that: (i) the pores of shale in the Niutitang Formation, Guizhou are mainly distributed within 1–100 nm, with a small total pore volume per unit mass, average pore diameter, large BET specific surface area and porosity; (ii) fractal dimension has a negative correlation with average pore diameter and TOC content and a quadratic relationship with BET specific surface area; and (iii) permeability has a positive correlation with Kn, porosity and fractal dimension. In the transitional diffusion zone, fractal dimension and porosity have a significant impact on permeability. In the Knudsen diffusion zone, porosity has no obvious effect on permeability. The methodologies and results presented will enable more accurate characterization of the complexity of pore structures of porous media and allow further understanding of the seepage law of shale gas.